Schoolness effect and academic journals: The case of the Revue de la Régulation (2007-2023) - Adrien Rougier (Revue de la Régulation)
This article focuses on the circulation of the label “school” in the social sciences, using the specific case of the so-called “Regulation school” and its journal. A bibliometric analysis of La Revue de la Régulation between 2007 and 2023 indicates that it stands out from other French-language economics journals due to its proximity to leading English-language heterodox economics journals, in terms of shared authorship and citation frequency. It is also peculiar in having a small group of authors who have published a significant portion of its articles, a high self-citation rate, and a strong concentration of citations around a few key figures. These features contribute to the common perception that there exists a “Regulation school”. This editorial and bibliographic core is associated with a form of pluralism, as evidenced by the average number of French-language economics journals in which the authors also publish, as well as the diversity of bibliographic references and journals cited. Lastly, the comparison with L’Année de la Régulation (1994-2005) reveals a significant decrease in the proportion of graduates from most prestigious French engineering schools among the authors and editorial board members, along with an increase in the share of women. It seems that this sociological shift has gone hand in hand with a diversification of research orientations. This suggests a great malleability of the term “school”, still applying despite variations and heterogeneity within the designated collective.